BSE BEHAVIOR IN YOUNG WOMEN BASED ON THE THEORY OF HEALTH PROMOTION MODEL - lubbanna aini alvin syah; Sri Utami; Juniastuti Juniastuti (UNIVERSITAS AIRLANGGA, 2022)
AbstractBackground: Breast cancer is the most common cancer in women, in East Java was 9,688 cases in 2013. The health promotion model is health promotion theory to regulate people behavior which aims to be primary prevention. Purpose: Identify the benefits, barriers and self-efficacy for students of SMKN 6 Surabaya. Methods: The study design used a cross-sectional. The independent variables in this study are perceived benefits, barriers to action, and self-efficacy. The dependent variable in this study was BSE behavior. The population of this study was all students of SMKN 6 Surabaya with the sampling technique using proportional random sampling. Data analysis used the chi-square correlation test. Results: From the results of this study, it was found that the majority of respondents who answered that there was a perceived benefit of 61.8%, there were no obstacles of 58.8%, there was 57.4% of self-ability, 80.9% of good knowledge, a good attitude at 85.3%, and less action at 61.8%. The results of the correlation test between perceived benefits and self-efficacy with breast self-examination or BSE behavior in adolescent girls had a relationship (p = 0.016 and p = 0.004). Meanwhile, the correlation test between barriers and BSE behavior in adolescent girls had no relationship p = 0.460. Based on the results of multivariate analysis, multiple logistic regression tests on the perceived benefits of BSE behavior obtained OR = 3.464 and p-value 0.023. Whereas for the results of multivariate analysis on self-efficacy with BSE behavior, the OR = 0.307 and p-value 0.029 were obtained. Conclusion:BSE behavior in young women is related to the perceived benefits and ability to do BSE.An additional curriculum on health of breast cancer.needs to be implemented in every school so that each student can carry out health promotion as a form of early prevention.